Nanoparticle-modified coatings by electrophoretic deposition for corrosion protection of magnesium. (3rd April 2022) - Akram, Muhammad; Arshad, Nasima; Braem, Annabel
ABSTRACT: Magnesium (Mg) and its biocompatible alloys are used as biodegradable materials for temporary implant applications. However, the fast electrochemical reactions in the physiological environment can lead to premature implant failure and damage the surrounding tissues. Here, we report on nanoparticle-modified biopolymer composite coatings processed using alternating current electrophoretic deposition (AC-EPD) to control the corrosion process of Mg–Al alloys. Chitosan–gelatin coatings incorporating bioactive glass particles as reinforcement were supplemented with ZnO and CeO2 nanoparticles and the corrosion resistance was evaluated. CeO2 nanoparticle-modified coatings obtained using AC signals superimposed with a direct current field appeared compact and homogeneous. ZnO nanoparticle-modified coatings had a low surface coverage with significant defects. As a result, CeO2 -supplemented coatings processed for as little as 4 min effectively reduced the corrosion current density ( i corr ) of Mg–Al in Ringer's solution, whereas ZnO-supplemented coatings did not. CeO2 nanoparticle-modified biopolymer coatings hold potential for fine-tuning the degradation of Mg implants.